PENERAPAN METODE SAW UNTUK MENENTUKAN DUGAAN REJECT BAN VULKANISIR BERDASARKAN KONDISI GEMBUNG DALAM - SIPAHUTAR, LAHMUDIN (Jurnal Sistem Informasi Kaputama (JSIK), 2019)
A company engaged in tire retreading is a company whose work process involves recycling worn tires by giving tire tread on the tire surface without changing the shape or brand on the base tire. During the production process there is tire damage. If there is a tire damage in the production process, then some of the vulcanized tires are not subject to production costs by the company. This certainly can make a loss for the company. Because a decision support system is needed to determine the dugaaned tire that must be rejected before recycling. The decision support system method suitable for this problem is the SAW Method with its web-based application.